IMPLEMENTASI NILAI-NILAI CATUR WARNA PADA PENDIDIKAN HINDU: KAJIAN PENDIDIKAN INFORMAL - Sukirno Hadi Raharjo (Bawi Ayah: Jurnal Pendidikan Agama dan Budaya Hindu, 2023)
In this modern life, the role of parents is demanded to be able to provide education and understanding of Hindu religious values, so that it is expected to be able to strengthen virtuous character education and improve children's learning achievements indirectly. Therefore this research was conducted to find out to what extent the values ​​of Catur Warna have been implemented by parents in educating their sons and daughters at home so that their children grow up to be superhumans. Catur warna means four choices in life or four divisions in life-based on one's talents (guna) and skills (karma), as well as the quality of work one has as a result of education, talent development that grows from within oneself and is supported by one's mental toughness in facing a job. The four groups that later became known as the Color Caturs were: Brahmins, Kshatriyas, Vaisyas, and Sudras. The method used is qualitative research with a descriptive approach where this method will provide a complete and complex picture of the data and facts obtained. Informal education in this case is a picture between parents and children in implementing Catuwarna values ​​in the family. The implementation of Catur Warna values ​​in informal education was found in this study, there were two parents' understanding of Caturwarna values ​​and implementation of values. -Caturwarna values ​​mean that parents must understand the context of Caturwarna which is then implemented in providing education to their children in strengthening the virtuous character of children.